2020
DOI: 10.3390/ijms21144983
|View full text |Cite
|
Sign up to set email alerts
|

Association between High On-Aspirin Platelet Reactivity and Reduced Superoxide Dismutase Activity in Patients Affected by Type 2 Diabetes Mellitus or Primary Hypercholesterolemia

Abstract: Platelet hyperactivation is involved in the established prothrombotic condition of metabolic diseases such as Type 2 Diabetes Mellitus (T2DM) and familial hypercholesterolemia (HC), justifying the therapy with aspirin, a suppressor of thromboxane synthesis through the irreversible inhibition of cyclooxygenase-1 (COX-1), to prevent cardiovascular diseases. However, some patients on aspirin show a higher than expected platelet reactivity due, at least in part, to a pro-oxidant milieu. The aim of this study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…Hypercholesterolemia stimulates platelet biogenesis through megakaryopoiesis, and leukocytosis by myelopoiesis, and increases platelet activation, by promoting platelet production and by direct impact on platelets [ 28 , 29 , 30 , 31 ]. The increased cholesterol level enhances the hyperaggregability of thrombocytes, too.…”
Section: Discussionmentioning
confidence: 99%
“…Hypercholesterolemia stimulates platelet biogenesis through megakaryopoiesis, and leukocytosis by myelopoiesis, and increases platelet activation, by promoting platelet production and by direct impact on platelets [ 28 , 29 , 30 , 31 ]. The increased cholesterol level enhances the hyperaggregability of thrombocytes, too.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Barale et al demonstrated that, in FH, platelet reactivity is correlated with biomarkers of redox function, including SOD and the in vivo marker of oxidative stress urinary 8-iso-prostaglandin F2α [167]. In addition, many authors observed, in FH in parallel to the high levels of LDLc, reduced GSH, SOD, and CAT levels, and increased ROS production [130,135,136] (Table 2).…”
Section: Hypercholesterolemiamentioning
confidence: 99%
“…Studies conducted on laboratory mice prove that GPx1 deficiency results in decreased protection from complications due to cardiac muscle damage, exacerbates ischemia-reperfusion injuries to cardiomyocytes, promotes endothelium dysfunction and structural irregularity of the cardiac muscle. Studies suggest that GPX3 is relevant in the proper functioning of the endothelium and the oxidation of low density lipoproteins (LDL) by the removal of soluble hydroxides, which is why GPX3 plays a role in preventing atherosclerosis [13,14]. GPX3 excess is also relevant, as it leads to myocardial hypertrophy [15].…”
Section: Resultsmentioning
confidence: 99%
“…GPX3 insufficiency leads to an increased platelet adhesion due to an increase in oxidative inactivation of NO. The impairment of physiological mechanisms inhibiting blood platelets promotes platelet hyperactivity leading to thrombosis [13]. GPX4 prevents LDL oxidation and can reduce hydroperoxides in endothelial cell membranes decreasing clotting [16].…”
Section: Resultsmentioning
confidence: 99%